Halloysite-based nano material modified composite membrane as well as preparation method and application thereof

By using electrostatic self-assembly technology in sulfonated polyimide matrix, hydroxylated eloxite and sulfonated eloxite are integrated to form a continuous proton transport network, solving the insufficient proton conductivity and ion exchange capacity of the existing proton exchange membranes. The problem of improving the mechanical properties and stability of the membrane.

CN119447389APending Publication Date: 2025-02-14HEBEI UNIV OF ENG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411586120.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The proton conductivity and ion exchange capacity of existing proton exchange membrane fuel cells are insufficient, and the mechanical strength and chemical stability of the materials are poor, making it difficult to form a continuous proton transmission channel.

Method used

By electrostatic self-assembly using hydroxylated elliptic and sulfonated elliptic in the sulfonated polyimide matrix, a continuous proton transport network is formed to improve proton conductivity and ion exchange capacity.

Benefits of technology

It has achieved the improvement of proton conductivity and ion exchange capacity in fuel cells, enhanced the mechanical properties and stability of the membrane, and extended the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447389A_ABST
    Figure CN119447389A_ABST
Patent Text Reader

Abstract

The invention provides a halloysite-based nano material modified composite membrane as well as a preparation method and application thereof, and belongs to the technical field of fuel cells. The preparation method comprises the following steps: self-assembling positive charge modified sulfonated halloysite and stripped zirconium phosphate to obtain a self-assembled compound, mixing the self-assembled compound with sulfonated polyimide, casting, and drying to form the membrane. The sulfonated tubular halloysite and the lamellar zirconium phosphate are adopted to form a continuous proton transmission network, so that the proton conduction rate and the ion exchange capacity of the membrane are greatly improved; electrostatic interaction can be formed between a composite structure of the formed self-assembled compound and a sulfonated polyimide matrix, so that the mechanical property and the stability of the membrane can be improved. The halloysite-based nano material modified composite membrane has excellent proton conduction rate and ion exchange capacity, is good in mechanical property and hydrolysis-resistant stability, and can be applied to fuel cells as a proton exchange membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a halloysite-based nanomaterial modified composite membrane and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane fuel cells are fuel cells with proton exchange membrane as the core. Compared with other fuel cells, they have the advantages of cleanliness and high efficiency, high energy conversion rate, no restrictions on Carnot cycle, no pollution during power generation, high specific power, simple structure, etc. The currently used perfluorosulfonic acid proton exchange membrane has good proton conductivity under low temperature and high humidity, but it also has disadvantages such as high cost, poor dimensional stability, low mechanical strength, and poor chemical stability.

[0003] At present, some methods have been proposed to solve the above problems. For example, patent CN105680077A invented a proton exchange membrane with good fluidity and processability. The titanium dioxide fluid of the invention is compounded with sulfonated polyetheretherketone solution, sulfonated polyphenylene ether, and polyaniline filtrate to increase proton conductivity and effectively reduce the methanol permeability of the composite proton exchange membrane. However, when the titanium dioxide doping amount is high, it may hinder the proton conduction channel and affect the overall proton conductivity of the membrane; patent CN106099146A invented a proton exchange membrane of sulfonated halloysite nanotube modified sulfonated polymer electrolyte. The prepared composite film has high proton conductivity. The rate and mechanical stability of the film are improved, and the presence of halloysite effectively inhibits the swelling of the film and improves the service life of the film, but it does not form a continuous proton transmission channel, which slows down the conduction of protons to a certain extent; Patent CN102863637A adopts heteropoly acid-phosphotungstic acid to be doped into a polyimide matrix, and the proton conductivity and alcohol resistance of the film prepared by it are improved, but due to the property that the heteropoly acid is easily soluble in water, it is very easy to be lost from the membrane, and the proton conductivity drops sharply; Patent CN102800881A discloses a method for preparing an inorganic proton exchange membrane for a fuel cell, which adopts a dispersant methyl cellulose ether to make ZrO 2 It is evenly dispersed in the proton exchange membrane, which improves the operating stability of the battery. However, methyl cellulose ether has poor high temperature resistance, resulting in a short service life of the proton exchange membrane.

[0004] In summary, the above modification methods cannot form a continuous network structure for proton conduction. Therefore, how to construct an effective proton transmission channel, improve the proton conductivity and ion exchange capacity of the membrane and maintain the intrinsic uniformity and stability of the membrane material needs further exploration. Summary of the invention

[0005] The object of the present invention is to provide a halloysite-based nanomaterial modified composite membrane and a preparation method and application thereof, which forms a continuous proton transmission channel in a sulfonated polyimide matrix and improves the proton conductivity and ion exchange capacity.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a halloysite-based nanomaterial-modified composite membrane, comprising the following steps:

[0008] Mixing halloysite, water and alkali to carry out a hydroxylation reaction to obtain hydroxylated halloysite;

[0009] The hydroxylated halloysite, the sulfonation agent and the entrainer are mixed to carry out a sulfonation reaction to obtain the sulfonated halloysite;

[0010] The sulfonated halloysite, the polymer modifier and water are mixed and subjected to electrostatic adsorption to obtain positively charged modified sulfonated halloysite;

[0011] Mixing zirconium phosphate, tris(hydroxymethyl)aminomethane) and water, and performing stripping to obtain a stripped zirconium phosphate dispersion;

[0012] Mixing the positively charged modified sulfonated halloysite with the stripped zirconium phosphate dispersion to perform self-assembly to obtain a self-assembled composite;

[0013] Mixing the self-assembled complex, sulfonated polyimide and an organic solvent to obtain a casting solution;

[0014] The casting solution is cast into a membrane, and the obtained composite membrane is subjected to proton exchange treatment in an acid solution to obtain a halloysite-based nanomaterial modified composite membrane.

[0015] Preferably, the alkali comprises sodium hydroxide; the mass ratio of the halloysite to the alkali is (1.8-2.2):(0.04-0.08); the temperature of the hydroxylation reaction is 25-35°C, and the time is 22-25h.

[0016] Preferably, the sulfonating agent includes 1,3-propane sultone, concentrated sulfuric acid or chlorosulfonic acid, and the entrainer includes toluene; the dosage ratio of the hydroxylated halloysite, the sulfonating agent and the entrainer is (0.9-1.1) g: (0.35-0.45) g: (50-60) mL; the temperature of the sulfonation reaction is 100-130° C., and the time is 22-25 h.

[0017] Preferably, the polymer modifier includes polydiallyldimethylammonium chloride, polyethyleneimine, chitosan or polylysine; the mass ratio of sulfonated halloysite to the polymer modifier is (0.9-1.1):(0.2-0.3); the temperature of the electrostatic adsorption is 25-35°C, and the time is 2-4h.

[0018] Preferably, the mass ratio of the zirconium phosphate to tris(hydroxymethyl)aminomethane is (1.8-2.1):(0.9-1.1); the stripping temperature is 25-35° C., and the stripping time is 30-35 min.

[0019] Preferably, the mass ratio of the sulfonated halloysite to zirconium phosphate is (2.8-3.2):(1.8-2.2); the temperature of the self-assembly is 25-35° C., and the time is 3-6 hours.

[0020] Preferably, the organic solvent comprises dimethyl sulfoxide; and the mass ratio of the self-assembled complex to the sulfonated polyimide is (1-10):(90-99).

[0021] Preferably, the acid solution comprises a sulfuric acid solution, and the concentration of the acid solution is 1.4 to 1.5 mol / L; and the proton exchange treatment time is 20 to 30 hours.

[0022] The invention provides a halloysite-based nano material modified composite membrane prepared by the preparation method.

[0023] The present invention also provides the use of the halloysite-based nanomaterial modified composite membrane as a proton exchange membrane in a fuel cell.

[0024] Beneficial effects of the present invention:

[0025] The present invention adopts a polymer modifier to modify sulfonated halloysite, and the modified sulfonated halloysite is positively charged; a stripping agent is adopted to perform stripping treatment on zirconium phosphate, and the surface of the stripped zirconium phosphate is negatively charged; the positively charged modified sulfonated halloysite and the stripped zirconium phosphate are assembled through electrostatic adsorption, and the one-dimensional and two-dimensional materials are assembled into a three-dimensional composite structure to form a continuous proton transport network, the sulfonated halloysite can provide more sulfonate radicals, and the zirconium phosphate as a super solid acid can provide more protons, thereby greatly improving the proton conduction rate and ion exchange capacity of the membrane.

[0026] The surface of the self-assembled complex formed by the positively charged sulfonated halloysite and the stripped zirconium phosphate has a positive charge, and the sulfonated polyimide has a negative charge due to the presence of sulfonate groups. The self-assembled complex can also form an electrostatic interaction with the sulfonated polyimide matrix, which is beneficial to improving the mechanical properties and stability of the membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1is a flow chart for the synthesis of sulfonated polyimide;

[0028] Figure 2 Zeta potential test results of the sulfonated halloysite, the positively charged modified sulfonated halloysite, the stripped zirconium phosphate, and the self-assembled complex in Example 2;

[0029] Figure 3 The SEM characterization images of the sulfonated halloysite, the zirconium phosphate after exfoliation, and the self-assembled composite in Example 2, wherein (A) is the sulfonated halloysite, (B) is the zirconium phosphate after exfoliation, and (C) is the self-assembled composite;

[0030] Figure 4 The SEM characterization images of the halloysite-based nanomaterial-modified composite membranes of Examples 1 to 3 and the polyimide proton exchange membrane of Comparative Example 1, wherein (A) is the polyimide proton exchange membrane of Comparative Example 1, (B) is the halloysite-based nanomaterial-modified composite membrane of Example 1, (C) is the halloysite-based nanomaterial-modified composite membrane of Example 2, and (D) is the halloysite-based nanomaterial-modified composite membrane of Example 3;

[0031] Figure 5 FTIR spectra of the halloysite-based nanomaterial modified composite membranes of Examples 1 to 3 and the polyimide proton exchange membrane of Comparative Example 1. DETAILED DESCRIPTION

[0032] The present invention provides a method for preparing a halloysite-based nanomaterial-modified composite membrane, comprising the following steps:

[0033] Mixing halloysite, water and alkali to carry out a hydroxylation reaction to obtain hydroxylated halloysite;

[0034] The hydroxylated halloysite, the sulfonation agent and the entrainer are mixed to carry out a sulfonation reaction to obtain the sulfonated halloysite;

[0035] The sulfonated halloysite, the polymer modifier and water are mixed and subjected to electrostatic adsorption to obtain positively charged modified sulfonated halloysite;

[0036] Mixing zirconium phosphate, tris(hydroxymethyl)aminomethane) and water, and performing stripping to obtain a stripped zirconium phosphate dispersion;

[0037] Mixing the positively charged modified sulfonated halloysite with the stripped zirconium phosphate dispersion to perform self-assembly to obtain a self-assembled composite;

[0038] Mixing the self-assembled complex, sulfonated polyimide and an organic solvent to obtain a casting solution;

[0039] The casting solution is cast into a membrane, and the obtained composite membrane is subjected to proton exchange treatment in an acid solution to obtain a halloysite-based nanomaterial modified composite membrane.

[0040] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.

[0041] The present invention preferably mixes halloysite with water, then adds alkali to make the solution pH=11.5-12, performs hydroxylation reaction, repeatedly filters and washes with water until neutral, pH=6.8-7.5, and then dries to obtain hydroxylated halloysite. In the present invention, the alkali preferably includes sodium hydroxide. The mass ratio of the halloysite to the alkali is preferably (1.8-2.2):(0.04-0.08), more preferably (1.8-2):(0.05-0.07), more preferably 2:0.06, and the volume of the water is preferably 10-100 mL. The temperature of the hydroxylation reaction is preferably 25-35° C., more preferably 28-33° C., more preferably 30° C., and the time is preferably 22-25 h, more preferably 23-24 h, more preferably 24 h. Hydroxylation of halloysite can increase the number of hydroxyl groups on the surface of the halloysite, which is beneficial to the subsequent sulfonation of the halloysite by a sulfonation reagent.

[0042] The present invention preferably mixes the hydroxylated halloysite, the sulfonating agent and the entrainer, performs a sulfonation reaction, and filters, washes and dries with acetone and chloroform to obtain the sulfonated halloysite; in the present invention, the sulfonating agent preferably includes 1,3-propane sultone, concentrated sulfuric acid (mass concentration is preferably 1.8 to 1.9 g / mL) or chlorosulfonic acid, and further preferably includes 1,3-propane sultone, and the entrainer preferably includes toluene; the dosage ratio of the hydroxylated halloysite to the sulfonating agent and the entrainer is preferably ( 0.9~1.1)g:(0.35~0.45)g:(50~60)mL, more preferably (0.9~1)g:(0.35~0.4)g:(55~60)mL, more preferably 1g:0.4g:60mL; the temperature of the sulfonation reaction is preferably 100~130℃, more preferably 100~120℃, more preferably 110℃, the time is preferably 22~25h, more preferably 23~25h, more preferably 24h.

[0043] The present invention preferably mixes a polymer modifier with water, mixes the obtained polymer modifier solution with sulfonated halloysite, and performs electrostatic adsorption to obtain positively charged modified sulfonated halloysite; in the present invention, the polymer modifier preferably includes polydiallyldimethylammonium chloride, polyethyleneimine, chitosan or polylysine, further preferably includes polydiallyldimethylammonium chloride or polyethyleneimine, and more preferably includes polydiallyldimethylammonium chloride; the concentration of the polymer modifier solution is preferably 0.008-0.015wt.%, further preferably 0.01-0.015wt.%, more preferably 0.01-0.012wt.%; the sulfonated The mass ratio of halloysite to the polymer modifier is preferably (0.9-1.1):(0.2-0.3), further preferably (0.9-1):(0.2-0.25), and more preferably 1:0.2; the temperature of the electrostatic adsorption is preferably 25-35°C, further preferably 25-30°C, and more preferably 30°C, and the time is preferably 2-4h, further preferably 2-3h, and more preferably 3h; since the polymer modifier carries a positive charge in its aqueous solution, it can electrostatically interact with the negatively charged sulfonated halloysite and undergo electrostatic adsorption, so that the surface of the sulfonated halloysite, which originally had a negative charge, becomes positively charged, thereby obtaining positively charged modified sulfonated halloysite.

[0044] In the present invention, tris(hydroxymethyl)aminomethane is preferably mixed with water, and then zirconium phosphate is added for stripping to obtain a zirconium phosphate dispersion after stripping; in the present invention, the mass ratio of the zirconium phosphate to tris(hydroxymethyl)aminomethane is preferably (1.8-2.1):(0.9-1.1), more preferably (1.8-2):(0.9-1), more preferably 2:1, and the volume of the water is preferably 100-150 mL; the stripping temperature is preferably 25-35°C, more preferably 25-30°C, more preferably 30°C, and the time is preferably 30-35 min, more preferably 30-33 min, more preferably 30 min.

[0045] The present invention preferably mixes the positively charged modified sulfonated halloysite with the stripped zirconium phosphate dispersion to perform self-assembly to obtain a self-assembled complex; in the present invention, the amount relationship between the positively charged modified sulfonated halloysite and the stripped zirconium phosphate dispersion is preferably calculated based on the mass ratio of sulfonated halloysite to zirconium phosphate, and the mass ratio of sulfonated halloysite to zirconium phosphate is preferably (2.8-3.2):(1.8-2.2), further preferably (2.8-3):(1.8-2), and more preferably 3:2; the self-assembly temperature is preferably 25-35°C, further preferably 25-30°C, and more preferably 30°C, and the time is preferably 3-6h, further preferably 4-6h, and more preferably 5h.

[0046] In the present invention, a sulfonated polyimide is mixed with an organic solvent, the obtained sulfonated polyimide solution is mixed with the self-assembled complex, and mechanically stirred for 5 to 8 hours to obtain a casting solution; the mass concentration of the sulfonated polyimide solution is preferably 4 to 10%, more preferably 4 to 6%, and more preferably 5%; the mass ratio of the self-assembled complex to the sulfonated polyimide is preferably (1 to 10): (90 to 99), more preferably (1 to 3): (97 to 99), and more preferably 2:99.

[0047] The present invention does not specifically limit the source of the sulfonated polyimide, and any conventional commercially available product or a product prepared by a conventional method may be used. In the embodiments of the present invention, the sulfonated polyimide is preferably prepared according to the document Synthesis and characterization of new sulfonated polyimides as proton-exchange membranes for fuel cells (doi: 10.1016 / j.memsci.2005.12.049).

[0048] In the present invention, the casting liquid is cast on a glass plate to form a film, and then dried at 60-80°C under normal pressure, and then vacuum dried at 80-100°C and 0.6-1MPa. The obtained composite membrane is first soaked in anhydrous ethanol for 1-2 hours, and then soaked in an acid solution for proton exchange treatment, washed with water until neutral, and dried by blast heating using nitrogen or argon at 100-130°C to obtain a halloysite-based nanomaterial modified composite membrane; the acid solution preferably includes a sulfuric acid solution, and the concentration of the acid solution is preferably 1.4-1.6 mol / L, and more preferably 1.4-1.5 mol / L; the time of the proton exchange treatment is preferably 20-30 hours.

[0049] The invention provides a halloysite-based nano material modified composite membrane prepared by the preparation method.

[0050] The present invention also provides the use of the halloysite-based nanomaterial modified composite membrane described in the above technical solution as a proton exchange membrane in a fuel cell.

[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0052] Example 1

[0053] 2 g of halloysite was mixed with water, NaOH was added to make the solution pH = 12, magnetic stirring was carried out for 24 h at a temperature of 30°C, hydroxylation reaction was carried out, the solution was filtered and washed with water repeatedly until neutral, pH = 7.0, and dried to obtain hydroxylated halloysite;

[0054] 1 g of hydroxylated halloysite was mixed with 60 mL of toluene and 0.4 g of 1,3-propane sultone, and the mixture was subjected to sulfonation reaction at 110°C for 24 h, and then filtered with acetone and chloroform for several times and washed and dried to obtain sulfonated halloysite;

[0055] 0.2 g of polydiallyldimethylammonium chloride was mixed with water, and the obtained polydiallyldimethylammonium chloride solution with a concentration of 0.01 wt.% was mixed with 1 g of sulfonated halloysite, and ultrasonicated for 3 h at a temperature of 30° C. to obtain positively charged modified sulfonated halloysite;

[0056] 2 g of zirconium phosphate was mixed with 150 mL of water and 1 g of tris(hydroxymethyl)aminomethane, with the mass ratio of zirconium phosphate to tris(hydroxymethyl)aminomethane being 2:1, and subjected to exfoliation, and subjected to ultrasonic treatment for 30 min at a temperature of 30° C. to obtain an exfoliated zirconium phosphate dispersion;

[0057] The positively charged modified sulfonated halloysite was mixed with the stripped zirconium phosphate dispersion, the mass ratio of the sulfonated halloysite to the zirconium phosphate being 3:2, and self-assembled at a temperature of 30°C for 5 hours to obtain a self-assembled composite;

[0058] The preparation process of sulfonated polyimide is as follows Figure 1 As shown, the diamine monomers used are 4,4'-diaminostilbene-2,2'-disulfonic acid and 4,4'-diaminodiphenyl ether, and the dianhydride monomer is 1,4,5,8-naphthalenetetracarboxylic anhydride;

[0059] The self-assembled complex and a dimethyl sulfoxide solution of sulfonated polyimide with a mass concentration of 5% were mixed, the mass ratio of the self-assembled complex to the sulfonated polyimide was 1:99, and mechanically stirred for 6 hours to obtain a casting solution;

[0060] The casting liquid was cast onto a glass plate to form a film, dried at 80°C under normal pressure and vacuum dried at 80°C and 1 MPa. The resulting composite membrane was first immersed in anhydrous ethanol for 2 h, then immersed in 1.5 mol / L sulfuric acid for 24 h for proton exchange treatment, washed with water until neutral, and dried by blowing heating with nitrogen at 120°C to obtain the halloysite-based nanomaterial modified composite membrane of Example 1.

[0061] Example 2

[0062] The only difference from Example 1 is:

[0063] The mass ratio of the self-assembled complex and sulfonated polyimide was 2:98;

[0064] The halloysite-based nanomaterial modified composite membrane of Example 2 was obtained.

[0065] Example 3

[0066] The only difference from Example 1 is:

[0067] The mass ratio of the self-assembled complex and sulfonated polyimide was 3:97;

[0068] The halloysite-based nanomaterial modified composite membrane of Example 3 was obtained.

[0069] Comparative Example 1

[0070] A 5wt.% sulfonated polyimide solution was cast onto a glass plate to form a film, and then dried at 80°C under normal pressure and vacuum dried at 80°C and 1MPa to obtain a sulfonated polyimide proton exchange membrane; the sulfonated polyimide proton exchange membrane was first soaked in anhydrous ethanol for 2h, and then soaked in 1.5mol / L sulfuric acid for 24h for proton exchange treatment, washed with water until neutral, and dried by blast heating at 120°C using nitrogen to obtain the sulfonated polyimide proton exchange membrane of Comparative Example 1.

[0071] Performance testing and characterization

[0072] The present invention uses a Zetapotential (Zetasizer Nano ZS90) instrument to measure the Zeta potential of the sulfonated halloysite, the positively charged modified sulfonated halloysite, the stripped zirconium phosphate, and the self-assembled complex in Example 2. The test results are as follows: Figure 2 Zeta potential can reflect the charged state of particles to a certain extent. Figure 2 It can be seen that both sulfonated halloysite and zirconium phosphate after stripping are negatively charged, and the Zeta potential value of sulfonated halloysite modified by polydiallyldimethylammonium chloride becomes +30.2mV. According to reports, positively charged substances and negatively charged substances can be easily combined together; the Zeta potential of the self-assembled composite becomes +22.3mV, which is caused by the neutralization of the charge in the composite material. The results also show the successful synthesis of the electrostatic self-assembled composite material of sulfonated halloysite and zirconium phosphate.

[0073] The present invention uses a scanning electron microscope to observe the surface structural characteristics of the sulfonated halloysite, the peeled zirconium phosphate, and the self-assembled composite in Example 2. Figure 3 As shown in (A), sulfonated halloysite is a one-dimensional tubular structure, such as Figure 3 As shown in (B), the peeled zirconium phosphate is a two-dimensional layer structure, and the self-assembled complex formed by combining the two through electrostatic interaction is as shown in Figure 3 As shown in (C), one-dimensional sulfonated halloysite and two-dimensional zirconium phosphate are combined to form a continuous three-dimensional structure, and the continuous structure greatly improves the proton conductivity of the film.

[0074] The present invention uses a scanning electron microscope to observe the surface structural characteristics of the halloysite-based nanomaterial-modified composite membranes of Examples 1 to 3 and the polyimide proton exchange membrane of Comparative Example 1. Figure 4 As shown in (A), the film of Comparative Example 1 is dense and smooth, while Figure 4 Middle (C), Figure 4 As shown in (D), the surface roughness of Example 2 and Example 3 gradually increased, indicating that the self-assembled complex was successfully added into the sulfonated polyimide matrix.

[0075] The present invention uses FTIR spectrometer to analyze the halloysite-based nanomaterial modified composite membranes of Examples 1 to 3 and the polyimide proton exchange membrane of Comparative Example 1, and obtains the following: Figure 5 Infrared spectrum shown. Analysis Figure 5 It can be seen that at 1660cm -1 and 1710cm -1 The stretching vibration peak of naphthalene imide is 1016 cm -1 and 1074cm -1 The peak at 1047cm is the stretching vibration peak of the sulfonic acid group. -1 Weaker stretching vibration peaks of OPO in zirconium phosphate were observed.

[0076] The present invention conducts the following performance tests on the halloysite-based nanomaterial modified composite membranes of Examples 1 to 3 and the polyimide proton exchange membrane of Comparative Example 1. The test results are shown in Table 1.

[0077] 1. Mechanical properties test: The film is made into rectangular strips and tested using a film tensile testing machine with a tensile speed of 5 mm / min and an original gauge length of 20 mm. The tensile formula is as follows:

[0078]

[0079] Where σ1 is the tensile strength (MPa), P is the maximum load (N), b is the specimen width (mm), and d is the specimen thickness (mm);

[0080] 2. Proton conductivity test: Use an electrochemical workstation and AC impedance method to test. Before the test, the membrane needs to be soaked in deionized water for 24 hours to fully hydrate the membrane. During the test, the membrane is clamped between the proton conductivity test fixtures. The test frequency range is 1Hz-100kHz. The conductivity σ calculation formula is as follows:

[0081]

[0082] Wherein: - proton conductivity (S / cm), L is the distance between the two levels (cm), R is the intrinsic impedance (Ω), d is the thickness of the membrane (cm), and w is the width of the membrane (cm);

[0083] 3. Ion exchange capacity

[0084] The acid-base titration method was used to test. 0.5-1g of the film was weighed and immersed in a 1mol / L NaCl solution for 24h. Then a few drops of phenolphthalein reagent were added and titrated with a 0.005mol / L NaOH solution until the solution was neutral. The volume of sodium hydroxide consumed was recorded. The IEC calculation formula is as follows:

[0085]

[0086] Where V NaOH is the volume of sodium hydroxide consumed (mL);

[0087] C NaOH is the concentration of sodium hydroxide (mol / L);

[0088] m is the mass of the membrane (g);

[0089] 4. Hydrolysis stability test

[0090] The film was dried in a vacuum oven at 120 °C for 10 h to obtain a film mass W 0 , and then placed it in deionized water at 80°C for 48h. The membrane was taken out and dried at 80°C for 8h, and then placed in a vacuum oven at 120°C for 10h to obtain the membrane mass W t , the hydrolytic stability (Wc) is calculated as follows:

[0091]

[0092] Where W c is the hydrolytic stability of the film (%);

[0093] W 0 is the mass of the dried film before testing (g)

[0094] W t is the mass of the dried film after the test (g);

[0095] 5. Water absorption

[0096] After the film was dried in an oven at 80°C for 24 hours, the weight of the sample (m 0 ) is measured when it reaches ambient temperature. After immersion in distilled water at 60°C for 8 hours, excess surface water on each sample is removed with filter paper within 30 seconds, and then its mass m is measured. 1 The water absorption WU can be calculated using the following formula:

[0097]

[0098] Where WU is the water absorption rate of the film (%);

[0099] m 1 The mass of the wet film of water on the surface wiped off after the test (g);

[0100] m 0 is the mass of the dry film before testing (g).

[0101] Table 1 Performance test results of the halloysite-based nanomaterial modified composite membranes of Examples 1 to 3 and the polyimide proton exchange membrane of Comparative Example 1

[0102]

[0103] As can be seen from Table 1, the halloysite-based nanomaterial modified composite membrane prepared by the preparation method of the present invention has a long-range ordered continuous proton transmission channel constructed inside the film due to the addition of the filler, and the presence of the super solid acid can also provide more protons, thereby improving the proton conductivity and ion exchange capacity of the composite film; while ensuring a high proton conductivity, due to the rigid structure of the filler itself and the good interface compatibility with the sulfonated polyimide matrix, the mechanical strength and stability of the proton exchange membrane are greatly improved, and the addition of the tubular structure halloysite greatly improves the water absorption rate of the film.

[0104] As can be seen from the above embodiments, the present invention provides a method for preparing a composite membrane modified by a halloysite-based nanomaterial, wherein sulfonated halloysite and zirconium phosphate are dispersed in an organic solution for electrostatic self-assembly, and then the obtained self-assembled composite is filled in a sulfonated polyimide solution, cast and dried to form a membrane. The halloysite-based nanomaterial-modified composite membrane obtained by the present invention has excellent proton conductivity and ion exchange capacity, good mechanical properties and hydrolysis resistance stability, and can be used as a proton exchange membrane in a fuel cell.

[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a halloysite-based nanomaterial-modified composite membrane, characterized in that: The following steps are involved: Mixing halloysite, water and alkali to carry out a hydroxylation reaction to obtain hydroxylated halloysite; The hydroxylated halloysite, the sulfonation agent and the entrainer are mixed to carry out a sulfonation reaction to obtain the sulfonated halloysite; The sulfonated halloysite, the polymer modifier and water are mixed and subjected to electrostatic adsorption to obtain positively charged modified sulfonated halloysite; Mixing zirconium phosphate, tris(hydroxymethyl)aminomethane) and water, and performing stripping to obtain a stripped zirconium phosphate dispersion; Mixing the positively charged modified sulfonated halloysite with the stripped zirconium phosphate dispersion to perform self-assembly to obtain a self-assembled composite; Mixing the self-assembled complex, sulfonated polyimide and an organic solvent to obtain a casting solution; The casting solution is cast into a membrane, and the obtained composite membrane is subjected to proton exchange treatment in an acid solution to obtain a halloysite-based nanomaterial modified composite membrane.

2. The preparation method according to claim 1, characterized in that: The alkali includes sodium hydroxide; the mass ratio of the halloysite to the alkali is (1.8-2.2):(0.04-0.08); the temperature of the hydroxylation reaction is 25-35° C., and the time is 22-25 hours.

3. The preparation method according to claim 1, characterized in that: The sulfonating agent includes 1,3-propane sultone, concentrated sulfuric acid or chlorosulfonic acid, and the entrainer includes toluene; the dosage ratio of the hydroxylated halloysite, the sulfonating agent and the entrainer is (0.9-1.1) g: (0.35-0.45) g: (50-60) mL; the temperature of the sulfonation reaction is 100-130° C., and the time is 22-25 hours.

4. The preparation method according to claim 1, characterized in that: The polymer modifier includes polydiallyldimethylammonium chloride, polyethyleneimine, chitosan or polylysine; the mass ratio of the sulfonated halloysite to the polymer modifier is (0.9-1.1):(0.2-0.3); the temperature of the electrostatic adsorption is 25-35°C, and the time is 2-4h.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the zirconium phosphate to tris(hydroxymethyl)aminomethane is (1.8-2.1):(0.9-1.1); the stripping temperature is 25-35° C., and the stripping time is 30-35 min.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the sulfonated halloysite to the zirconium phosphate is (2.8-3.2):(1.8-2.2); the temperature of the self-assembly is 25-35° C., and the time is 3-6 hours.

7. The preparation method according to claim 1, characterized in that: The organic solvent includes dimethyl sulfoxide; the mass ratio of the self-assembled complex to the sulfonated polyimide is (1-10):(90-99).

8. The preparation method according to claim 1, characterized in that: The acid solution includes a sulfuric acid solution, and the concentration of the acid solution is 1.4 to 1.5 mol / L; the proton exchange treatment time is 20 to 30 hours.

9. The halloysite-based nanomaterial modified composite membrane prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the halloysite-based nanomaterial modified composite membrane according to claim 9 as a proton exchange membrane in a fuel cell.

Citation Information

Patent Citations

  • Preparation method for inorganic proton exchange membrane of fuel cell

    CN102800881A

  • Preparation method of phosphotungstic acid-polyimide composite proton exchange membrane

    CN102863637A

  • Proton exchange membrane

    CN105680077A

  • Modified halloysite nanotube for proton exchange membrane and preparation method of modified halloysite nanotube

    CN106099146A